Role for a Novel Signaling Intermediate, Phosphatidylinositol 5-Phosphate, in Insulin-Regulated F-Actin Stress Fiber Breakdown and GLUT4 Translocation - Sbrissa, Diego; Ikonomov, Ognian C.; Strakova, Jana; Shisheva, Assia (Endocrinology (Philadelphia), 2004)
The cellular functions and regulation of phosphatidylinositol (PtdIns) 5-phosphate (5-P), the newest addition to the family of phosphoinositides (PIs), are still elusive. Here we have examined a plausible role of PtdIns 5-P as a signaling intermediate in acute insulin action. A wortmannin-insensitive transient increase of PtdIns 5-P mass levels that peaked at 10 min, and declined 20–30 min after insulin stimulation, was observed in both Chinese hamster ovary (CHO)-T cells stably expressing the insulin receptor and 3T3-L1 adipocytes. Similarly to insulin, found to induce a rapid disassembly of Texas-Red phalloidin-labeled actin stress fibers in CHO-T cells, microinjected PtdIns 5-P, but not other PIs, decreased the number and length of F-actin stress fibers in this cell type to a magnitude seen in response to insulin. Likewise, increases of PtdIns 5-P by ectopic expression of the PtdIns 5-P-producing enzyme PIKfyve yielded a similar effect. As with insulin, the PtdIns 5-P-induced loss of actin stress fibers was independent of PI 3-kinase activation. Furthermore, sequestration of functional PtdIns 5-P, either by ectopic expression of 3xPHD domains that bind selectively PtdIns 5-P or by microinjecting the GST-3xPHD fusion peptide, abrogated insulin-induced F-actin stress fiber disassembly in CHO-T cells. In 3T3-L1 adipocytes, microinjected PtdIns 5-P, but not other PIs, partially mimicked insulin’s effect of translocating enhanced green fluorescent protein-GLUT4 to the cell surface. Conversely, insulin-induced myc-GLUT4 vesicle dynamics was arrested in the presence of coexpressed enhanced green fluorescent protein-3xPHD. Involvement of PIKfyve membrane recruitment, but not activation, and/or a decrease in PtdIns 4,5-bisphosphate levels are likely to be among the mechanisms underlying the insulin-induced PtdIns 5-P increase. Together, these results identify PtdIns 5-P as a novel key intermediate for insulin signaling in F-actin remodeling and GLUT4 translocation.